Regional Economic Issues, Central, Eastern, and Southeastern Europe : How to Get Back on the Fast Track. (Regional Economic Outlook, 2016)
This paper discusses the robust growth that continues in most Central and Southeastern European economies as well as in Turkey. Accommodative macroeconomic policies, improving financial intermediation, and rising real wages have been behind the region's mostly consumption-driven rebound, while private investment remained subdued. In the near-term, strong domestic demand is expected to continue supporting growth amid continued low or negative inflation. The Russian economy went through a sharp contraction last year amid plunging oil prices and sanctions. Other CIS countries were hurt by domestic political and financial woes, as well as by weak demand from Russia. In 2016, output contraction is projected to moderate to around 1 1\2 percent from 4u percent in 2015 as the shocks that hit the CIS economies gradually reverberate less and activity stabilizes. In the baseline, a combination of supportive monetary policy and medium-term fiscal consolidation remains valid for many economies in the region.